Factors influencing issuers' sukuk structure preference : the case study of KSA banks - Hussain, Hanadi Abu Baker N (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
The Purpose of this research paper is to examine the impact of Sukuk on the performance of the Kingdom of Saudi Arabia (KSA) Sukuk issuing listed banks and the factors that influence the issuers Sukuk structures using the pooled OLS regression and the random effect panel data models. Despite of the high R-squared and the overall significance of both of the pooled OLS regression models (1A and 2A) as well as the random effects model (1B), however, we report only the findings of the random effect model (2B) due to its consistency with theory. Hence, the results of the study suggest that bank size and amounts of issued Sukuk affect the KSA listed banks performance positively at 5% level of significance whereas the leverage ratio affects them negatively at 1% level of significance. Nevertheless, the dummy Sukuk though not significant, the negative magnitude clearly indicates the profit maximization aspect. Therefore, we may conclude that even though Sukuk impacts the KSA Sukuk issuing banks performance positively, the factors that influence the issuers Sukuk structures is profit maximization rather than Shariah compliance. Finally, the findings of this research paper may provide some policy insights to practitioners, policymakers and some Shariah scholars in the KSA.